An Investigation into the Attitudes of Pre-Service Teachers towards Teaching Children with Special Educational Needs - Munroe, Aoife (My University, 2019)
This article investigates the attitudes of pre-service teachers towards teaching children with SEN. Understanding the views of pre-service teachers as they climb onto the first step in their professional career is essential to provide the support required to facilitate progression as they navigate the complexities of teaching. The findings of this study present interesting results in terms of beliefs about inclusion, the impact of the type of SEN on a pre-service teacher’s attitude and their selfbelief. In addition to this, it is crucial to recognise how impactful attitudes can be, with negative attitudes identified as ‘a major barrier’ to inclusion by a UNESCO report in 2005. While participants in this study were predominantly positive towards teaching children with SEN, it was interesting to learn about the factors that challenged these attitudes.
Journal article
Keywords: Research Subject Categories::SOCIAL SCIENCES; Primary Education; Teaching; Special Education; ITE; STER